2014
DOI: 10.1016/j.epag.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Application of different scoring systems and their value in pediatric intensive care unit

Abstract: Background: Little is known on the impact of risk factors that may complicate the course of critical illness. Scoring systems in ICUs allow assessment of the severity of diseases and predicting mortality. Objectives: Apply commonly used scores for assessment of illness severity and identify the combination of factors predicting patient's outcome. Methods: We included 231 patients admitted to PICU of Cairo University, Pediatric Hospital. PRISM III, PIM2, PEMOD, PELOD, TISS and SOFA scores were applied on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 26 publications
4
13
1
Order By: Relevance
“…In our study, inotropes requirement for >6 hours was considered, where those who needed inotrope support consisted of 22 patients out of which 19 died. Inotropes requirement had statistically significant correlation with mortality ( p = 0.0000), corroborating the findings by Rady et al 11 in his study as compared to other studies who found that higher mortality in patients using these drugs. The association of PELOD-2 with outcome obtained suggested maximum mortality in the group with score >15 (66.6%) ( Table 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, inotropes requirement for >6 hours was considered, where those who needed inotrope support consisted of 22 patients out of which 19 died. Inotropes requirement had statistically significant correlation with mortality ( p = 0.0000), corroborating the findings by Rady et al 11 in his study as compared to other studies who found that higher mortality in patients using these drugs. The association of PELOD-2 with outcome obtained suggested maximum mortality in the group with score >15 (66.6%) ( Table 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…[9] The Pediatric Risk of Mortality (PRISM) score uses clinical, physiological and laboratory variables in the first 24 hours of PICU admission, to attain a score assessing severity of illness. [10] Although validated for use in the USA, [11] its validity in an SA population has been questioned. [12] The Paediatric Index of Mortality (PIM) score is a simpler tool using eight parameters to assess mortality risk on admission.…”
Section: Researchmentioning
confidence: 99%
“…In this comparison of five scoring systems 6 ( Table 1 ), where score for each patient was calculated on all scoring systems, it was seen that there was very good correlation among all different systems used. Hence, it probably matters very little what system is used in a unit.…”
mentioning
confidence: 89%